Studies on Character Associations and Path Coefficient Analysis in Rice bean [Vigna umbellata (Thunb.) Ohwi and Ohashi] Germplasm - Singh, M.; Kumar, V. (International Journal of Bio-resource and Stress Management, 2018)
The correlation and path coefficient analysis were carried out with 28 diverse genotypes of rice bean including three checks viz., PRR-1, PRR-2 and BRS-1 were evaluated in Randomized Complete Block Design with three replications. The characters studied were days to 50 per cent flowering, days to maturity, plant height, stem thickness, number of primary branches per plant, leaflet size , number of pods per plant, number of seeds per pod, pod length,100 seed weight and seed yield per plant. Grain yield per plant exhibited very strong positive association with number of pods plant-1, pod length, leaflet size, number of seeds pod-1 and number of primary branches at phenotypic and genotypic level. Path- coefficient analysis was carried out at genotypic as well as phenotypic level, identified number of pods per plant as major positive direct contributors followed by number of seeds pod-1, leaflet size and plant height to seed yield plant-1. Number of pods plant-1 and number of seeds pod-1 exhibited high order positive indirect effect on seed yield plant-1 via pod length whereas, number of pods plant-1 followed by leaflet size exhibited highest positive indirect effect on seed yield. The characters identified above merit due consideration in formulating effective selection strategy in rice bean for developing high yielding varieties.